Characterization of spawning and nursery grounds of Hilsa, Tenualosa ilisha (Hamilton 1822) based on larval and juvenile distribution and feeding habits - Rashid, Md. Harunor (2020)
Hilsa (Tenualosa ilisha) is a migratory fish within the Bay of Bengal region and is mostly harvested from the waters of Bangladesh. The Meghna River is the main corridor for hilsa migration from Bay of Bengal of Bangladesh which provides the major habitat for spawning and movement migration. The abundance of hilsa in Meghna River varies from year to year and the knowledge of the effect of environmental factors on distribution and abundance of hilsa larvae and juveniles in the Meghna River still now absent. Hence, the study was conducted to characterize the spawning and nursery grounds of hilsa based on larva and juvenile distribution in relation to environmental parameters in the Meghna River and its tributaries in Bangladesh. A total of nine sampling stations from August 2017 to January 2018 for hilsa larvae and 18 sampling stations for hilsa juveniles from February to April 2017 were surveyed monthly using bongo net (mouth diameter of 50 cm with 400 μm of mesh size) and experimental net (2.5, 3.5, 4.5 and 5.5 cm of mesh sizes), respectively. The environmental parameters i.e., water temperature (oC), salinity (‰), dissolved oxygen (DO in mg/L), pH (1-14), conductivity (μS/cm); total dissolved solids (TDS in mg/L) and rainfall (mm) data were recorded monthly from the selected areas. The study showed that the highest mean larvae density (37.77 ± 5.64 ind. m-3) was observed in lower parts followed by the middle (33.07 ± 10.27 ind. m-3) and it was absent in upper stretches of the river. The abundance of hilsa larvae were statistically similar (p > 0.05) in lower and middle stretches but was significantly different (p < 0.05) compared to the upper stretches of the Meghna River. The highest mean larvae density was observed in September 2017 (61.07 ± 15.56 ind. m-3), where it could not be found in January 2018. The abundance of hilsa larvae in the Meghna River was statistically similar (p > 0.05) in the months of September, October, and November, but the abundance was significantly different (p < 0.05) from August 2017 and December 2017. Bray-Curtis similarity index and nonmetric multidimensional scaling (nMDS) clearly separated the lower and middle parts from upper stretches of Meghna River and had 77 % similarity in terms of larval abundance. In the hilsa larvae study, significant variations (p > 0.05) of environmental parameters were found among the study zones except for water temperature and rainfall. The water temperature was highest (28.72±1.09 oC) in the upper and lowest (24.59±1.15 oC) in the middle zone of the river. Salinity, pH and conductivity were highest as 0.67±0.16 ‰, 7.40±0.07 and 388.16±29.05 μS/cm, respectively in the lower zone and lowest as 00±0.00 ‰, 6.89±0.16 and 226.08±14.57 μS/cm, respectively in the upper zone of the river. DO and TDS were highest as 7.41±0.05 mg/L and 154.71±21.63 mg/L, respectively in the middle and lowest as 6.70±0.27 mg/L and 92.73±14.79 mg/L, respectively in the upper zone of the river. Furthermore, highest rainfall (290.67±99.26 mm) was recorded at upper and lowest (205.03±35.64 mm) from the lower zone of the river. The non-parametric Spearman’s correlation analysis showed the larval abundance was greatly influenced (p < 0.05) by temperature, DO, pH and TDS. Principal component analysis (PCA 1, PCA 2 and PCA 3) showed that temperature, salinity, DO, pH, and conductivity explained 83.5% of the larvae variations in the study areas. However, biotic-environmental (BIO-ENV) analysis showed that water temperature, salinity, and pH played significant role (p < 0.05) in the hilsa larval distribution. On the other hand, the highest mean juvenile abundance was found in the middle river stretch (58.33 ± 14.64 ind./100 m net/30 min), followed by the lower (27.39 ± 6.03 ind./100 m net/30 min) and upper (2.17 ± 0.78 ind./100 m net/30 min) stretches of the river. There were significant differences in juvenile abundances (p < 0.05) among the study areas. However, no significant differences (p > 0.05) of juvenile abundance were observed among the months during the study period. Bray-Curtis similarity index indicated the lower, middle, and upper stretches of the river had only 46 % similarity in terms of juvenile hilsa distribution. In the hilsa juvenile study, salinity showed significant variations (p > 0.05) among the zones. The highest (1.34±0.29 ‰) salinity was recorded from lower and lowest (00±0.00 ‰) in the upper zone of the river. Temperature, pH, DO, conductivity, TDS and rainfall did not show variations (p < 0.05) among the zones. The non-parametric Spearman’s correlation analysis showed the juvenile abundance was significantly (p < 0.05) correlated with salinity, pH, and TDS. Principal component analysis (PCA 1, PCA 2 and PCA 3) showed that temperature, salinity DO, pH and TDS explained 75.7% of the hilsa juvenile variations in the study areas. However, biotic-environmental (BIO-ENV) analysis showed juvenile distribution was highly dependent on salinity (p < 0.05). The study also revealed that phytoplankton including Bacillariophyceae (eleven genera), Chlorophyceae (four genera), Cyanobacteria (six genera) and Euglenophyceae (two genera), and zooplankton including Protozoa (three genera), Rotifera (seven genera), Copepoda (five genera), Cladocera (five genera), Ostracoda (one genus) and Chaetognatha (one genus) were observed in the juvenile gut analysis. The juvenile gut content also showed that phytoplankton and zooplankton formed 91 % and 4 % of the total food, respectively, indicating that hilsa juveniles were highly dependent on phytoplankton. Therefore, habitat location, time, feed availability and environmental parameters influenced the distribution of hilsa in the study area. The study illustrated information on hilsa larva and juvenile distribution in relation to environmental parameters could provide important evidence for locating major hilsa spawning and nursery areas to effectively protect this important resource in Bangladesh waters.